The Use of Coronectomy to Manage Symptomatic Mandibular Third Molars: Techniques, Pitfalls and Suggested Guidelines. (2nd March 2021) - Bolt, Robert; Hirani, Murtaza; Kyriakidou, Elena; El-Awa, Abdurahman; Atkins, Simon; Shah, Preeni
Abstract : Coronectomy is a valuable technique in the management of symptomatic mandibular third molars at high risk of inferior alveolar nerve injury. When applied appropriately, the technique may reduce the incidence of inferior alveolar nerve injury in comparison to full surgical removal. Currently, no definitive guidelines exist on when to opt for coronectomy versus full surgical removal, and therefore significant variation in clinical practice exists. This article summarizes the surgical stages involved in the coronectomy procedure, reviews the indications and hazards of the technique, and finally provides suggested guidelines to assist the practitioner in the decision-making process of when to opt for coronectomy versus full surgical removal in the management of symptomatic mandibular third molars. CPD/Clinical Relevance: To review the coronectomy technique and highlight potential hazards with inappropriate application of the technique.